2021
DOI: 10.1002/fsn3.2279
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25‐hydroxyvitamin D concentrations and obesity in one‐year‐old Chinese infants

Abstract: Recent studies suggested that vitamin D is linked with obesity, but evidence in infants is scarce. Therefore, we aimed to make an exploration in infants. A total of 414 infants at one year old who visited Maternity and Child Health Care Hospital of Wuxi in China were recruited. Finger‐stick blood sampling was conducted in all the subjects, and serum 25‐hydroxyvitamin D [25(OH)D] concentrations were measured. Maternal characteristics during pregnancy and infantile information were collected by questionnaires or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…One cross-sectional study carried out in 2021 also found the same relationship, where the increased risk of infancy overweight/obesity was attributed to VitD deficiency; inverse linear relationships were observed between 25(OH)D level and body mass index as well as BMI z-score in one-year-old infants [35]. In this study, they found that infants with a deficient VitD status had a 2.74-fold increased risk for obesity [41]. Although there has been limited research on the impact of VitD on infant overweight/obesity, these findings are promising and warrant more investigation, such as extending the follow-up period or developing multicenter trials across cities.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…One cross-sectional study carried out in 2021 also found the same relationship, where the increased risk of infancy overweight/obesity was attributed to VitD deficiency; inverse linear relationships were observed between 25(OH)D level and body mass index as well as BMI z-score in one-year-old infants [35]. In this study, they found that infants with a deficient VitD status had a 2.74-fold increased risk for obesity [41]. Although there has been limited research on the impact of VitD on infant overweight/obesity, these findings are promising and warrant more investigation, such as extending the follow-up period or developing multicenter trials across cities.…”
Section: Discussionsupporting
confidence: 62%
“…In our study, the suboptimal 25(OH)D level of <35 ng/mL for infants at 6 months significantly increased the risk for overweight/obesity at 12 months. There is considerable evidence that school-aged children and adolescents with a 25(OH)D level <20 ng/mL are susceptible to overweight/obesity [19,41,43]. Esmaili et al pointed out that a higher level of 25(OH)D of 30 ng/mL was a risky inflection point [18].…”
Section: Discussionmentioning
confidence: 99%